Identifying the Ideological Social Construct: What are its Implications for Sociology? (Groundings Undergraduate, 2015)
In contemporary western discourse the concept of the social fact has gradually been diluted in favour of what many activists refer to as the ‘social construct’. However, this approach to constructivism is not truly sociological, and is based on discourse rather than analysis. This has led to a rise in ‘pop’ sociology. The first half of this article will explore what I have deemed the ‘ideological social construct’, its origins in western discourse and its relation to contemporary identity politics. The second half will focus on possible reconstructive methods for the harm that the ideological social construct has done to social science methodology.
Keywords: Identity Politics; Social Fact; Ideology; Social Construct; Reconstructive methods; Methodology; Critical Review